2009
DOI: 10.1007/978-3-642-00596-1_32
|View full text |Cite
|
Sign up to set email alerts
|

Realizability Semantics of Parametric Polymorphism, General References, and Recursive Types

Abstract: Abstract. We present a realizability model for a call-by-value, higherorder programming language with parametric polymorphism, general first-class references, and recursive types. The main novelty is a relational interpretation of open types (as needed for parametricity reasoning) that include general reference types. The interpretation uses a new approach to modeling references.The universe of semantic types consists of world-indexed families of logical relations over a universal predomain. In order to model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 22 publications
0
40
0
Order By: Relevance
“…(On the other hand, those examples have also shown that, with the help of Lemma 2, our "brute-force" method is often simple enough.) Logical relations are also better at giving a compositional model of universal types, as in [3] and [6,7].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(On the other hand, those examples have also shown that, with the help of Lemma 2, our "brute-force" method is often simple enough.) Logical relations are also better at giving a compositional model of universal types, as in [3] and [6,7].…”
Section: Resultsmentioning
confidence: 99%
“…A recent paper by Ahmed, Dreyer and Rossberg [3]discussed in Section 1, 7 and 8-follows this line of work. Another line of work has been carried out by Birkedal et al [6][7][8]. To the best of our knowledge, our method can prove strictly more examples of equivalences than all of the above approaches (though this is hard to prove generally, because completeness by itself does not always mean an automatic proof; recall that observational equivalence is undecidable in our language).…”
Section: Related Workmentioning
confidence: 94%
See 1 more Smart Citation
“…To reflect this, several semantic models of weak references in the literature follow the "possible worlds" approach [2,10,16,34]. There, the interpretation of a type is parameterized over a world, which represents the current state of the store.…”
Section: Which Intermediate Language?mentioning
confidence: 99%
“…. [10] or work with approximate solutions of it [2,14]. An alternative is to define a world as a map of memory addresses to syntactic types [16].…”
Section: Which Intermediate Language?mentioning
confidence: 99%